A CASE STUDY ON AMAVATA W.S.R TO RHEUMATOID ARTHRITIS (International Journal of Food and Nutritional Sciences, 2022)
Amavata is composed of two elements: "Ama" and "Vata." This condition is primarily caused by an imbalance in Agni, including Jatharagni, Dhatvagni, and Bhutagni, leading to the formation of Ama. The Ama then spreads throughout the body via vitiated Vata, accumulating in areas such as Shleshmasthana (e.g., Amashaya, Asthisandhi), resulting in pain, stiffness, and swelling in both small and large joints, ultimately leading to immobility. The clinical symptoms of Amavata are similar to those of rheumatoid arthritis, an inflammatory autoimmune disease characterized by chronic, destructive, and deforming symmetrical polyarthritis, often with systemic involvement. In India, the prevalence of rheumatoid arthritis ranges from 0.5% to 3.8% in women and 0.15% to 1.35% in men.Allopathic treatments provide symptomatic relief but often fail to address the underlying pathology, resulting in potential side effects and adverse reactions. In contrast, Ayurvedic treatment not only avoids these issues but also provides a more comprehensive approach by addressing the root cause—Agni and Ama. Management of Amavata in Ayurveda includes therapies such as langhana (fasting or lightening measures), Swedana (sudation therapy), and the use of herbs with tikta (bitter), katu (pungent) tastes, as well as deepana and pachana (digestive and metabolic enhancers) for Shamana chikitsa (palliative care). The first detailed description of Amavata as a disease is found in Madhav Nidan, which provides a systematic understanding of Amavata and its Ayurvedic management5.